2020
DOI: 10.1371/journal.pone.0234650
|View full text |Cite
|
Sign up to set email alerts
|

An analytical study of neocartilage from microtia and otoplasty surgical remnants: A possible application for BMP7 in microtia development and regeneration

Abstract: To investigate auricular reconstruction by tissue engineering means, this study compared cartilage regenerated from human chondrocytes obtained from either microtia or normal (conchal) tissues discarded from otoplasties. Isolated cells were expanded in vitro, seeded onto nanopolyglycolic acid (nanoPGA) sheets with or without addition of bone morphogenetic protein-7 (BMP7), and implanted in nude mice for 10 weeks. On specimen harvest, cartilage development was assessed by gross morphology, histology, and RT-qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Earlier investigations from this and other laboratories have established the experimental basis for such an avenue with auricular cells grown in hydrogels or on a variety of polymers designed as sheets, discs or 3D ear-shaped scaffolds [4][5][6]. The present examination follows more recent reports that human conchal and microtia chondrocytes are equivalent and may each be utilized experimentally to regenerate tissue-engineered auricular cartilage [7][8][9].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Earlier investigations from this and other laboratories have established the experimental basis for such an avenue with auricular cells grown in hydrogels or on a variety of polymers designed as sheets, discs or 3D ear-shaped scaffolds [4][5][6]. The present examination follows more recent reports that human conchal and microtia chondrocytes are equivalent and may each be utilized experimentally to regenerate tissue-engineered auricular cartilage [7][8][9].…”
Section: Discussionmentioning
confidence: 88%
“…Subsequent developments in auricle reconstruction have been made through several basic science investigations, in which animal and human chondrocytes have been utilized to design engineered auricle constructs [4][5][6]. Related studies have also shown that normal (conchal) and microtia chondrocytes from otoplasty are effectively equivalent for engineered auricular cartilage regeneration [7][8][9]. Additional advances in auricle fabrication by means of preclinical studies have been reported, demonstrating satisfactory human auricle tissue-engineered grafts [10].…”
Section: Introductionmentioning
confidence: 99%
“…A further important balancing mechanism for cartilage tissue is the perpetuation of an intact ECM, which consists of collagen, elastins, and proteoglycans ( 39 ), and, due to its high water binding, has both a protective and nutritional function ( 40 ). As an advantage, our results pointed to CA’s support of Coll II, CSPG, and thus ECM synthesis and the expression of cartilage-specific transcription factor Sox9 ( Figure 5A ), suggesting a holistic, broad-based positive influence on PCH despite an OA-promoting environment.…”
Section: Discussionmentioning
confidence: 99%
“…These co-culture systems using ADSCs or other MSCs, combined with AuCs, demonstrate advantageous paracrine signaling that may mimic the native cell-cell interactions lost through the enzymatic digestion and processing of the cells 94 . As a result, this new microenvironment is conducive to functionally stable AuCs 84,87,95,96 . Moving forward, more attention should be focused on a means to optimize this microenvironment so that a clinically relevant expansion of chondrocytes can be achieved in a consistent, predictable manner.…”
Section: Tissue Engineeringmentioning
confidence: 99%